1984
DOI: 10.1017/s0022112084002536
|View full text |Cite
|
Sign up to set email alerts
|

Integral-equation solution of potential flow past a porous body of arbitrary shape

Abstract: Potential flow past a porous body of arbitrary shape with constant physical permeability k0, as well as the flow in the corresponding porous medium, are analysed by means of a pair of linear Fredholm integral equations of the second kind. As an example for verification of the proposed general method, the case of a two-dimensional porous circular cylinder is worked out in detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 2 publications
2
9
0
Order By: Relevance
“…It is observed that, when = 0 in (32), the resultant expression for F x agrees with that of the potential flow past a circular cylinder, given in Power et al (1984).…”
Section: Methods Of Solutionsupporting
confidence: 64%
See 4 more Smart Citations
“…It is observed that, when = 0 in (32), the resultant expression for F x agrees with that of the potential flow past a circular cylinder, given in Power et al (1984).…”
Section: Methods Of Solutionsupporting
confidence: 64%
“…In contrast with the case of Power et al (1984) of a porous circular cylinder of constant permeability where the total force is independent of the cylinder size, in this case the total force is a function of the characteristic radius r 1 of the slightly deformed cylinder and the radius r 2 of the circular core. In Fig.…”
Section: Methods Of Solutionmentioning
confidence: 94%
See 3 more Smart Citations